(untitled) (Baghdad Science Journal, 2024)
The effect of barley seed extracts on the corrosion of carbon steel in 1M hydrochloric acid at different temperatures was investigated from the perspective of their potential use as green inhibitors in the cleaning and descaling processes in heat exchangers. A 50% ethanol/water (vol) solution was used for extraction. Two extraction methods were used: soaking and ultrasound. The inhibition mechanism of the inhibitor that gave the best efficiency was investigated by studying the adsorption and corrosion processes by electrochemical methods (potentiodynamic polarisation (Tafel curves) and electrochemical resistance spectroscopy) and thermodynamic calculations. The results of the study showed no effect of the extraction method on the inhibition behavior, the inhibition as a function of concentration showed a significant increase in the inhibition efficiency up to concentration 400 ppm, then it appeared independent of it in both methods. However, the inhibition efficiency of the soaking method was higher at 800 ppm (87.01% compared to 80% for the ultrasound method). The study of the inhibition mechanism of this extract indicated the possibility of chemical adsorption. Inhibition activity increased with temperature.